(untitled) (GESTIÓN Y TENDENCIAS, 2019)
All of us need to work, but who takes care of caregiving duties while we work, and how, has not always been a matter of public interest. For a long time it has been a problem that we women have had to face and resolve alone, without help from men, from those who employ us, or from the State. This is unjust and unsustainable. We must socialize both the problem and the solutions if we want to guarantee that everyone can enter the labor market without compromising the care of those in our charge. But we must also do so if we want to be happy: it is not only a question of justice or economics, it is also a question of humanity, of happiness.